Extramedullary Relapse in a CML Patient after Allogeneic Stem Cell Transplantation. (21st March 2017) - Yilmaz, Asu Fergun; Soyer, Nur; Ozsan, Nazan; Cagirgan, Seckin; Gunes, Ajda; Comert, Melda; Sahin, Fahri; Saydam, Guray; Gunel, Nur Selvi; Vural, Filiz
Abstract : Myeloid or granulocytic sarcoma (GS) is a tumoral lesion consisting of immature granulocytic cells. It is a rare entity during the course of CML patients especially after allogeneic stem cell transplantation (SCT). Relapse without bone marrow involvement is much rarer. We report a case of CML patient who relapsed with isolated granulocytic sarcoma after allogeneic SCT during cytogenetic and molecular remission. 28-year-old male was diagnosed as CML and allogeneic SCT was performed because of refractory disease to tyrosine kinase inhibitors. Complete cytogenetic and molecular response was achieved after allogeneic SCT followed by dasatinib treatment. Approximately 5 years after the transplantation, very rapidly progressive lesion was documented and diagnosed as GS although he was at molecular and cytogenetic remission. The patient died during chemotherapy due to sepsis. GS relapse after allogeneic SCT is a very rare type of relapse in CML patients with molecular and cytogenetic remission. Since it is a very aggressive disease with a poor prognosis, combined chemoradiotherapies with other possible options like DLI or second allogeneic SCT should be considered as soon as the diagnosis is confirmed.